Remote sensing technologies for digital soil mapping: applications for agriculture and environmental planning - Mello, Fellipe Alcantara de Oliveira (2022)
This doctorate thesis developed advanced research regarding digital soil mapping (DSM) and its potential for improving soil surveys using multiple and complex digital information. For the first chapter, it is presented a general introduction to the developed research, a general contextualization of the topic\'s importance and its applications for the advancement of soil science. The second chapter presents the insertion of new covariates for the DSM related to drainage networks (DN). The work combined satellite, relief, and DN information to map clay, sand, and soil organic carbon contents for the municipality of Piracicaba in the state of São Paulo, Brazil. The third chapter applies the DSM methodology to refine (enhance the scale) a geological map for the Pereira Barreto region in the state of São Paulo, Brazil. The work showed that even with the soil surface spectra, it is possible to analyze the characteristics of the subsurface. In the fourth chapter, the bare soil detection methodology (Synthetic Soil Image SySI) was applied to identify and classify soils with hydromorphism. The reflectance in the visible, near-infrared and short-wave infrared (Vis-NIR-SWIR) spectral bands of the exposed soil was able to identify features related to hydromorphic soils, which were used to predict hydromorphic soils for a region of 863,577.9 km2 between the Southeast and Midwest of Brazil. The results showed a high occurrence of hydromorphism in agricultural areas, indicating the need for greater monitoring. The last chapter presents a general conclusion of the work with the main results and their applications for soil science.